2021
DOI: 10.1038/s41598-021-01282-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and optical properties of PMMA films reinforced with Nb2O5 nanoparticles

Abstract: The article presents the thermal and physical properties of PMMA composite films with the addition of Nb2O5 nanoparticles. The addition of nanoparticles to PMMA mainly influenced the optical transmission and glass transition temperature of composite films compared to pure PMMA. It is clearly visible in the results of the conducted ellipsometric and differential scanning calorimetry tests. X-ray studies showed that the heat treatment of the samples resulted in the ordering of the polymer structure (flattening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Thermal analysis was performed in two ways: using variable-temperature spectroscopic ellipsometry and differential scanning calorimetry. As in our previous works [ 29 , 30 , 31 , 32 ], here we present the variability of the ellipsometric angle Δ as a function of temperature for one selected wavelength. In this case, λ = 900 nm, due to the low dispersion of the measured points.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Thermal analysis was performed in two ways: using variable-temperature spectroscopic ellipsometry and differential scanning calorimetry. As in our previous works [ 29 , 30 , 31 , 32 ], here we present the variability of the ellipsometric angle Δ as a function of temperature for one selected wavelength. In this case, λ = 900 nm, due to the low dispersion of the measured points.…”
Section: Resultsmentioning
confidence: 93%
“…It turns out, as in our earlier works [ 29 , 30 , 31 , 32 ], that the variable-temperature spectroscopic ellipsometry (VTSE) non-destructive optical technique is very sensitive to thermal transitions and is very complementary to differential scanning calorimetry (DSC) with regard to the examination of organic layers. Literature data show that the identification of the characteristic temperatures of thermal transitions can be made on the basis of raw ellipsometric data [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] and additionally confirmed by an appropriate analysis of layer thickness changes caused by temperature change or various physical parameters [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 90%
“…The second mode allows us to measure Ψ and Δ under thermal annealing, in heating or cooling cycles alternatively. Usually, this mode is used for thermal transition investigations, in low vacuum conditions, as in our earlier works [ 35 , 36 , 37 , 38 ]. In this study, due to the need to monitor the surface changes, with a built-in optical microscope, all measurements were made in atmospheric air conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier works, VTSE was used in correlation with differential scanning calorimetry (DSC) [ 35 , 36 , 37 ] and temperature resistance measurements [ 38 ], as alternative, confirmative methods. In the work of Mei and Chung, it was shown that electrical resistance can be useful in studying the thermal properties and thermal history of carbon-fiber-reinforced nylon-6 composites [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer/inorganic oxide composites often exhibit different material properties compared to pure polymers. They often differ from pure polymers in their optical, thermal and electrical properties [11]. The present work aims to fabricate of PVA/PEG/In2O3 nanostructure from PVA/PEG as matrix and In2O3 nanoparticles as additive and studying the A.C electrical properties with different frequencies and In2O3 nanoparticles contents to use in various electronics nanodevices.…”
Section: Introductionmentioning
confidence: 99%